Building Customer Loyalty Formed by Price Fairness, Brand Familiarity Mediated by Trust in PT. Rosalia Express Customer - Yuliantini Yuliantini; Dian Artanti Arubusman; Muhammad Rizki; Ramzy Adib Sulaiman (Jurnal Ilmu Multidisiplin, 2025)
The aim of this research is to empirically analyze the influence of price fairness and brand familiarity on loyalty mediated by trust in PT. Rosalia Express customers in Indonesia. This research is descriptive quantitative, the analysis method used is SEM-PLS (Structural Equation Model - Partial Least Square) Smart PLS 4.0 software. With a number of respondents as many as 175 people taken by purposive sampling. The research results show that trust is an intervening variable that can significantly influence the relationship between price fairness and brand familiarity on customer loyalty.